2018
DOI: 10.1016/j.seizure.2018.01.024
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of scoring tools for the prediction of in-hospital mortality in status epilepticus

Abstract: EMSE-EAL is as easy to calculate as STESS and tended towards higher diagnostic accuracy. Adding information on premorbid functional status to STESS did not enhance outcome prediction. END-IT was not superior to other scores in prediction of in-hospital mortality despite including information of diagnostic work-up and response to initial treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 23 publications
0
33
1
Order By: Relevance
“…The AUC of STESS and EMSE were relatively low in our study, ranged between 0.6–0.7. Most previous studies from different geographic regions reported similar figures, ranged from 0.5–0.7 [7,13,14], except two studies reported AUC ranged between 0.7–0.89 for both tests [21,22]. The reason for lower AUC may be due to the samples size and different ethnicity studied in this cohort.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…The AUC of STESS and EMSE were relatively low in our study, ranged between 0.6–0.7. Most previous studies from different geographic regions reported similar figures, ranged from 0.5–0.7 [7,13,14], except two studies reported AUC ranged between 0.7–0.89 for both tests [21,22]. The reason for lower AUC may be due to the samples size and different ethnicity studied in this cohort.…”
Section: Discussionmentioning
confidence: 55%
“…Recently, a study investigated the accuracy of STESS, modified STESS, EMSE-EAL (EMSE including only etiology, age, and level of consciousness), and END-IT in outcome-prediction for in-hospital mortality. The results indicated a low specificity for STESS, balanced sensitivity-specificity ratio for END-IT, and high specificity for EMSE [7]. However, EEG data (used for EMSE outcome-predication) of the patients were excluded, and ENT-IT was not performed in every patient due to unavailable of brain image.…”
Section: Introductionmentioning
confidence: 99%
“…Patients' characteristics A total of 129 adult patients with incident, first-time status epilepticus were analyzed in this study. 19.4% of the patients had an acute symptomatic cause or suffered from progressive brain disease (1 patient with Lewy body disease, all others suffered from malignant brain tumors) as defined in [31]. EEG showed SE with or without predominant motor symptoms in 78% of all patients.…”
Section: Resultsmentioning
confidence: 99%
“…In the original publication, STESS with a cut-off of ≥3 achieved the highest accuracy [5]. However, later studies suggested that a cut-off of ≥4 has a more favorable sensitivity and specificity [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation